Pengaruh Media Audiovisual terhadap Kemampuan Menulis Teks Persuasi Siswa Kelas VIII SMP Negeri 7 Kota Bengkulu - Heryanto, Michel Fransiska; Yulistio, Didi; Noermanzah, Noermanzah (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Audiovisual media has the advantage of being able to attract students' attention and motivation because it combines sound and images. By providing audiovisual media, it is predicted to be able to influence students' ability to write persuasive texts. For this reason, this study aims to determine the effect of audiovisual media on the ability to write persuasive texts for class VIII students of SMP Negeri 7 Bengkulu City. This study uses a quantitative approach and quasi-experimental methods by comparing pre-test and post-test scores after using audio-visual media in learning to write persuasive texts. The population of this study were all students of class VIII SMP Negeri 7 Bengkulu City with a sample using a purposive sampling technique, namely on the basis of the objective of a quasi-experimental design for one class that was homogeneous so that 30 students from class VIII-A were taken. Data collection techniques using essay test techniques. The data analysis technique uses hypothesis testing with the paired t-test formula. Prerequisite test is done normality test using the chi-square formula. The results of the study show that there is an influence of audiovisual media on the ability to write persuasive texts. This is evidenced by the tcount > ttable test, namely 7,570 > 2,045. If seen from the sign (2-tailed) that is 0.000 <0.05 then Ho is also rejected and Ha is accepted.